Macromedia Dreamweaver MX UTILIZATION FOR WEB ORCHID RESOURCES - Nuria Delina(30403115); Marzuki Marzuki., SKom., MMSI (Jurnal Sistem Informasi, 2007)
Basis for it from the Web cultivation of this orchid is about the many people who think that empower membudi orchids are a difficult thing to do. In the Web orchid cultivation was discussed on the procedures empower membudi orchids. Web Creation This orchid cultivation using Macromedia Dreamweaver MX. With the internet technology we can make the information through an attractive web design and can be accessed quickly and easily. With this website, is expected to convey information about the manner of orchids membudi empower and simple to the general public.